METODE PELAKSANAAN PEKERJAAN SALURAN IRIGASI SEKUNDER D.I SIGULAI KABUPATEN SIMEULUE (MYC) - Susi Purnama Sari; Zulyaden Zulyaden (KOLONI, 2022)
In civil engineering work, a method must be needed in carrying out work in a project. In the work of air structures such as irrigation buildings, it is very necessary to carry out work in the field according to what has been planned. In the construction of irrigation networks there are earthworks which are the land where the pavement is built, which consists of soil, soil stockpiles, heavy equipment which are important factors in projects, especially large-scale construction projects, project management and implementation work plans, quality and quantity of materials used. will be used. The method of carrying out the work of the Sigulai secondary irrigation channel, which discusses the implementation of the survey. The research survey was conducted at D.I Sigulai which is in West Simeulue, Simeulue Regency. In the implementation of secondary irrigation canal work, survey work is carried out in seven months using theodolite, Waterpass, Meter, Compass, Clinometer, and Total Station. This study uses two data, the first is primary data which is the result of measurements and surveys, namely, coordinate data for the location of irrigation buildings and data which includes: area of ​​irrigation areas, maps of Sigulai irrigation areas, irrigation network schemes and irrigation building schemes obtained from Banda Aceh Water Service. The research results obtained that in the manufacture of secondary irrigation canals and auxiliary buildings there is a method of carrying out the work which consists of: Execution of ordinary earthworks, ordinary soil embankments, concrete layers, and concrete work floors is carried out using heavy equipment and the work of workers in their work, which is carried out during 24 (twenty four) months and the execution of complementary building works consisting of ordinary earthworks, concrete work floors, formwork, reinforcement, installation of river stones, plastering, and broadcasting is carried out using heavy equipment and laborers in the work, which is carried out for 10 (twenty four) months ten) months. Keywords: secondary, sigulai, Theodolite, Waterpass, Meter, Compass, Banda Aceh, simeulue